(untitled) (Linguostylistic Studies, 2018)
This article is an attempt to clarify one of the most productive means of forming and enriching Polish ecological terminology. As Ecology is a branch of science that is continuously developing, it is important to investigate sources from which terms are borrowed. Polish ecological terminology is formed both on the basis of specific Polish vocabulary and by borrowing from other languages. The fact is that not a single language is self-sufficient enough to provide the creation of terminological units with its own resources without using word-forming patterns and lexical units of other languages. Foreign elements in the Polish ecological term system are classified into terminological loanwords, non-terminological loanwords and grammatical borrowings. The article highlights a number of theoretical issues, including the status of terminological borrowing against the traditional distinction of core vs. cultural borrowings and the phenomenon of internationalisms. To summarize, Polish ecological terms include foreign words, loan words and partial substitution. Most of the international terms were transferred to the Polish ecological terminology from Greek, Latin, German, French, Italian and other languages. Having been adapted graphically, phonetically, morphologically, and semantically, foreign borrowings of ecological terminology, in their turn, demonstrate high word-forming activity. Borrowings are one of the most productive ways to replenish the lexical composition of the ecoterminology of the Polish language. The use of foreign terms makes it possible to fit naturally into the world of scientific and technical context.